Some Hatchery Parameters of Three Species of Groupers: Tiger Grouper (Epinephelus fuscoguttatus), Humpback Grouper (Cromileptes altivelis), and Leopard Coral Grouper (Plectropomus leopardus) - Suko Ismi; Darmawan Setia Budi (HAYATI Journal of Biosciences, 2022)
Three species of groupers, including tiger grouper (Epinephelus fuscoguttatus), humpback grouper (Cromileptes altivelis), and leopard coral grouper (Plectropomus leopardus), have been successfully cultivated. However, the constraints on larviculture that have been described still arise in the hatchery. This study compares several hatchery parameters in these three grouper species representing three different genera (Epinephelus, Cromileptes, and Plectropomus). The egg incubation and larval rearing were carried out in a concrete tank (3 x 3 x 1.2 m3) filled with 6-7 m3 seawater. Eggs were stocked with a density of 100,000 eggs/tank. The grouper larvae were reared until they became juvenile. The eggs were incubated until they were hatched in the same container and media as larval rearing. Larvae were reared until 60 dah (days after hatching), and data were taken from the rearing for three cycle's larval culture. Management of grouper larval rearing follows the Good Fish Hatchery Method (Cara Pembenihan Ikan yang Baik/CPIB) based on Indonesian National Standard (Standar Nasional Indonesia/SNI). The experimental parameters were egg diameter, hatching rate, larvae mouth opening width, survival activity index (SAI), larvae development, and total body length growth. The several hatchery parameters in three grouper fish species are significantly different. The tiger grouper has the best larval performance.